Implementation of graphic organizers to improve learning in mathematics and english subjects - Pérez García, Patricia Marlene (UCV Hacer, 2015)
The research called: Implementation of graphic organizers to improve learning in Math and English subjects in high school students in the fifth-grade in Institución Educativa “José Leonardo Ortiz”, it is an experimental investigation which use several strategies in high school students in the fifth-grade to evaluate the effectiveness of the implementation of graphic organizers to improve learning and making significant achievements in Mathematics and English subjects and contrast the new learning with the results obtained which have allowed systematizing our information. In order for the student to be an active individual in the process of learning to learn, it is important to teach effective strategies which help to plan regulate and evaluate learning. The main object is that student master a series of learning strategies, self-regulates their knowledge and develops meaningful learning and as a consequence becomes a strategic, thoughtful, capable and self-taught. The results we have obtained are positive. The implementation of Graphic Organizers determined the effective achievement of capacities in the fifth high school students demonstrated by the results of an arithmetic average in the experimental group in English 13.9 and Mathematics 12.2 on the vigesimal scale. This shows that our research is valid, the hypothesis is verified and this will serve to take corrective measures in the classroom regarding the use of Graphic Organizers as a teaching and learning strategy facilitating the achievement of skills in high school students in the fifth-grade of the Institución Educativa “José Leonardo Ortiz”.